Formulation Designing Factors for Development of Repaglinide Transdermal Therapeutic System (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Repaglinide, a blood-glucose-lowering drug, has a shorter half-life (~1 hour), low oral bioavailability (LOB) (~56 %) due to the first-pass metabolism, and required frequent dosing (Three to four times daily) to control blood glucose level. Repaglinide transdermal therapeutic system (TTS) was prepared to provide continuous drug delivery for a prolonged time. Designing factors for development are selection and optimization of product ingredients, optimization of drug load, types of TTS, matrix thickness, and optimization of drug delivery. During development, repaglinide TTS were evaluated for physicochemical characteristics and ex-vivo skin flux at different stages. Based on the pre-formulation study data, Durotak 87-2516® was selected as a pressure-sensitive adhesive. Different formulations of a drug in adhesive matrix and reservoir type repaglinide TTS were evaluated for ex-vivo skin permeation (flux) study. The skin flux results show that sandwiched reservoir type repaglinide TTS can provide average cumulative drug permeation and flux rate of 379.75 ± 47.89 μg/cm2 and 4.62 ± 1.00 μg/cm2/hr respectively for sustain drug delivery over the time of 72 hours. Developed sandwiched reservoir type repaglinide TTS has the potential to sustain delivery of drug for 72 hours, which reduce frequent dosing and thereby improve patient compliance.